1 Answer | Add Yours
You need to know that the process of composition of two functions is represented by the following notation(left) and the following result(right), such that:
`(fog)(x) = f(g(x))`
You should remember that if a problem requests to find the value of a function f(x), at a point x = a, you need to substitute a for x in equation of the function.
The same process works in composition of two function, thus, if the problem requests to find f(g(x)), you need to substitute g(x) for x in equation of f(x).
Since an worked example will make you better understand the process of composition, you may consider the following two functions, `f(x) = x^2` and `g(x) = 7x+5` .
You need to find `(fog)(x)` such that:
`(fog)(x) = f(g(x)) ` (first you need to write the result of composition)
`f(g(x))= (g(x))^2` (substitute g(x) for x in equation of f(x))
`f(g(x)) = (7x+5)^2` (replace g(x) with its equation)
`f(g(x)) = 49x^2 + 70x + 25` (raise the binomial to square using the formula `(a+b)^2 = a^2 + 2ab + b^2` )
Hence, evaluating the result of composition of the functions f(x) and g(x) yields `f(g(x)) = 49x^2 + 70x + 25` .
Thus, the compositions of functions use the rules of substitution, as it is shown in the previous example, hence `(fog)(x) = f(g(x)).`
We’ve answered 317,487 questions. We can answer yours, too.Ask a question